Pharmaceutical management of acute radiation dermatitis in the German speaking radiation oncology community: original article - Layer, Julian; Layer, Katharina; Glasmacher, Andrea; Sarria, Gustavo R.; Böhner, Alexander M. C.; Layer, Yonah L.; Dejonckheere, Cas S.; Wiegreffe, Shari; Nour, Youness; Caglayan, Lara; Grau, Franziska; Feyer, Petra; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Background Radiation dermatitis (RD) remains the most common side effect in radiation therapy (RT) with various pharmaceutical options available for prevention and treatment. We sought to determine pharmaceutical management patterns of radiation dermatitis among radiation oncology professionals. Methods We conducted a survey on RD among the German-speaking community of radiation oncologists inquiring for their opinion on preventive and therapeutic pharmaceutical approaches for acute RD. Results 244 health professionals participated. Dexpanthenol lotion is the agent most widely used both for prevention (53.0%) and treatment (76.9%) of RD, followed by urea (29.8%) for prevention and corticosteroids (46.9%) for treatment. A wide range of substances is used by participants, though the overall experience with them is rather limited. 32.5% of participants do generally not recommend any preventative treatment. 53.4% of participants recommend alternative medicine for RD management. While seldomly used, corticosteroids were considered most effective in RD therapy, followed by dexpanthenol and low-level laser therapy. A majority of participants prefers moist over dry treatment of moist desquamation and 43.8% prescribe antiseptics. Conclusions Pharmaceutical management of RD in the German-speaking radiation oncology community remains controversial, inconsistent, and partially not supported by evidence-based medicine. Stronger evidence level and interdisciplinary consensus is required amongst practitioners to improve these care patterns.